PERFORMANCE AUDITING IN THE PUBLIC SECTOR: RECONCEPTUALISING THE TASK - Kells, Stuart; Hodge, Graeme (The journal of contemporary issues in business and government, 2009)
Performance auditing (PA) is a prominent feature of public administration in many countries and is, today, often characterised through words such as efficiency, effectiveness and economy. The PA literature, however, considers a far wider variety of characteristics to be relevant and, therefore, a broader definition to be appropriate. This paper reviews the history of definitions of PA and concludes that it has thus far been defined in ways that lack clarity and leave definitional difficulties unresolved. The paper adopts a heuristic approach in examining elements making up past PA definitions and concludes that it is time to reconceptualise PA. Hence a new definitional framework for PA is proposed which rejects the so-called three Es construct and instead offers the five elements of independence, authorisation, discovery, synthesis and publication. This framework, it is argued, is stronger than any previous definitions, relevant to both the public and private sectors and also helpful in interpreting the place of many alternatives to PA such as investigative journalism, open book policies, whistleblower legislation and Gateway Reviews.